Peran Kepemimpinan dalam Meningkatkan Profesionalisme Guru Madrasah Aliyah di Bengkulu - Heri Kurniawan; Irma Yofita Sari; Fatimah Nurlatifah; Desta Zalza Bellah; Fariza Nur Utami; Muhammad Irvan Hamidi (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: The leadership role of madrasah has created difficulties in improving teacher professionalism, marked by some Aliyah madrasah teachers having difficulty in carrying out their main duties, functions and responsibilities as professional teachers and some other teachers are able to carry them out professionally. The purpose of this study is to map and describe the role of leadership in improving the professionalism of Aliyah madrasah teachers in Bengkulu. Using descriptive qualitative methods, with information sources in this study, using various sources, both online media data and print media data. Includes scientific books, scientific articles both national and international related about the role of leadership in improving teacher professionalism. The results of the study can be concluded that there are still some madrasah leadership that has not played an optimal role, it can be seen that decision making has not been brave and not decisive, has not focused on work programs, communication and leadership management of the head of the madrasah is not good, and control is still not continuous, so that there are still teachers who are less professional in learning, it can be seen that there are still some teachers who do not master their fields of knowledge, His teaching materials, learning methods, lack of motivation, lack of skill and his insight is still narrow. Thus, it can be suggested to improve teacher professionalism, then increase the leadership role optimally.Keywords: Role, Leadership, Teacher Professionalism, Madrasah Aliyah. Abstrak: Peran kepemimpinan madrasah telah menciptakan kesulitan dalam meningkatkan profesionalisme guru, ditandai dengan sebagian guru madrasah Aliyah mengalami kesulitan dalam melaksanakan tugas pokok, fungsi dan tanggungjawabnya sebagai guru professional dan sebagian guru yang lain mampu melaksanakannya secara profesional. Tujuan penelitian ini untuk memetakan dan mendeskripsikan peran kepemimpinan dalam meningkatkan profesionalisme guru madrasah Aliyah di Bengkulu. Menggunakan metode kualitatif deskriptif, dengan sumber informasi dalam penelitian ini, menggunakan berbagai sumber, baik data media online maupun data media cetak. Meliputi buku-buku ilmiah, artikel ilmiah baik nasional maupun internasional yang terkait tentang peran kepemimpinan dalam meningkatkan profesionalisme guru. Hasil penelitian dapat disimpulkan bahwa masih terdapat sebagian kepemimpinan madrasah belum berperan secara optimal, terlihat dalam pengambilan keputusan belum berani dan belum tegas, belum fokus pada program kerja, komunikasi dan manajemen kepemimpinan kepala madrasah kurang baik, serta pengontrolan masih kurang kontinyu, sehingga masih terdapat guru yang kurang professional dalam pembelajaran, terlihat masih terdapat sebagian guru kurang menguasai bidang ilmunya, bahan ajarnya, metode pembelajarannya, kurang motivasi, kurang terampil dan wawasannya masih sempit. Dengan demikian dapat disarankan untuk meningkatkan profesionalisme guru maka tingkatkanlah peran kepemimpinan secara optimal.Kata kunci: Peran, Kepemimpinan, Profesionalisme Guru, Madrasah Aliyah. Halamnan nanti, biar tim pengelola jurnal yang urus.